MATLAB based Design for an 8-point Discrete Fourier Transform formed on Products of Rademacher Functions - Roslidar, Roslidar; Zulfikar, Zulfikar (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This article discusses a DFT 8-point design based on Rademacher functions. The design is conducted based on previous research, a DFT 4-point model, for hardware. In general, the design requires two calculations of DFT 4-point, four counting processes of DFT 2-point, and three multiplying processes of twiddle factor. The adjustment has been made to change the path process from concurrent to sequential in order to adapt to the software execution command. The designed algorithm is run in MATLAB. The result shows that there is no difference between the proposed DFT and the one provided in MATLAB. Confidently, this design can be an alternative in transforming information signal into frequency domain using DFT technique.